CORN FERTILIZATION USING SWINE WASTEWATER AND SOIL-WATER ENVIRONMENTAL QUALITY - Rosa, Danielle M.; Sampaio, Silvio C.; Pereira, Pamela A. M. [UNESP]; Dos Reis, Ralpho R.; Sbizzaro, Mariana (Soc Brasil Engenharia Agricola, 2017)
Soil application of swine wastewater for nutrient cycling may represent a correct destination of these residues and reduction in production costs. However, when applied to soil, such residue may cause environmental impacts. This study aimed to analyze the chemical characteristics of the soil, corn, and leachate after successive swine wastewater applications associated with mineral fertilization. The experiment was developed in drainage lysimeters under field conditions. Wastewater doses applied were 0, 100, 200, and 300 m(3) ha(-1) with and without mineral fertilization. The results were submitted to analysis of variance and Tukey's test. After nine years of application, a special attention should be taken regarding water quality from a dose of 200 m(3) ha(-1) since some elements may leach into the soil. In addition, a synchronism between residue application and crop requirements needs to be taken into account. Doses of 200 and 300 m(3) ha(-1) are considered as satisfactory to meet corn nutritional requirements. Moreover, an increase in fertility characteristics was observed, but a caution regarding Cu and Zn contents should be taken since these elements produce a cumulative effect in the soil.
Keywords: liquid residue of swine; no-tillage; water reuse